Bedside assessment of reactive oxygen species (ROS) production within blood appears valuable as a predictive marker of mortality in patients with severe COVID-19 - Dündar, Nazlıhan Boyacı; Sarphie, David; Yüce, Kenan; Gaygısız, Ümmügülsüm; Kaskatı, Tolga; Turkoglu, Melda; Aygencel, Gulbin; Karabiyik, Lale; Çağlar, Kayhan; Bozdayi, Gulendam; Mian, Rubina; Moss, Paul; et al. (Journal of critical care, 2024)
A prompt and effective immune response is required for clearance of pathogens, but exaggerated states of inflammation can cause extensive collateral damage to the host. The measurements of the functional of neutrophils to produce reactive oxygen species (ROS) can be useful for this discrimination with severe COVID-19 or sepsis patients. Here we aimed to assess the utility of longitudinal ROS measurements to monitor and predict mortality outcome for patients with COVID-19 infection being treated in an intensive care unit (ICU). The study was conducted with ethical committee approval in the ICU of a university hospital. The patient population consisted of patients who were admitted to the ICU due to COVID-19 pneumonia; the healthy volunteer population consisted of healthcare workers from the hospital. ROS production in response to phorbol 12-myristate 13-acetate (PMA) stimulation was analyzed within 30 min of collection. Together with a range of conventional hematological tests and clinical observations, the LIT test was performed every day or every other day (except on weekends) until death or discharge 30 from the ICU. The Leukocyte ImmunoTest™ (LIT™, Seroxo, Oxford, UK) was used for ROS production. Results showed significantly higher values in the patient group (p < 0.01) with a predicted marginal LIT mean of 1557 for patients and 234 for healthy subjects (Table 1). The LIT values with matched neutrophil count values (PMNL) within the patient and healthy group, LIT values were found to correlate strongly with PMNL values and support the assessment of the LIT score as a measure of the functional capacity of within blood (Spearman's correlation 0.75 (0.59–0.86); p-value <0.05). When we assed the linear mixed effects model in relation to COVID-19 mortality; LIT/N values showed a trend to a progressive decrease for patients who survived compared to those who did not (Fig. 1). This predictive trend was not seen with measurement of PMNL or CRP and indicated that LIT/N may represent an important prognostic value in this group. Our results suggest that the LIT and LIT/N values produced by the test are valuable prognostic markers for clinical improvement or deterioration and have distinct advantages over current laboratory-based assays.